Methods of teaching innovative technologies in the content of education at universities (Journal of Educational Sciences, 2017)
This article says that the development of the educational system allows a direct impact on social conditions and increase their numbers in society. At the end of the 80s in the Republic of Kazakhstan adopted amodular system of education, when the process has been demonstrated the effectiveness of this system. In higher education, one goal has been dedicated to the preparation of textbooks in all subjects, and considering the importance of the educational content of the modular system. In the study, teaching law and not at the level of epistemological and practical skills to keep the priority of its activities, there are also automatically sent into action. The empirical paradigm in university teaching her expertise regarding criticism or scientific basis for the practice of other scientists who work through the press. Empirical paradigm today accumulated in respect of each faculty in the process of modernization, based on the theory and practice of implementation will be addressed. The mind of each person was to move steadily forward long operation was collected and spiritual values are offended quality for future generations.
Keywords: the education system; social society; an innovative system